Trauma in Rapes and Assaults - Jean-Michel (MDPI AG, 2021)
Psychological trauma primarily affects children and adolescents; it mostly results from physical and sexual maltreatment. In the Medico-Judicial Unit Center for Sexual Violence Victims in Tours, France, which I joined in 1992 for research and to give treatment, underage patients represented about three-quarters of patients. At the same time, a national survey was conducted in collaboration with Marie Choquet's "Adolescent Health" group (INSERM), which targeted several thousand adolescents representing the general population. It revealed that almost one out of five adolescents had experienced physical or sexual assault, and that although the number of sexual assaults probably does not exceed that of physical assaults, most of the time their psychological consequences do considerably exceed those of physical assaults. Several symptoms appear after experiencing rapes or assaults. They have a distinct semiology and independent evolutions. We isolated three of them: dissociative and phobic traumatic syndrome, re-experiencing traumatic syndrome, and borderline-like traumatic syndrome. They are generally triggered all at the same time or in close succession. Re-experiencing traumatic syndrome is profound, but the other two are often more worrying, particularly in relation to children and adolescents, because they generate disorders in their psychological development.